Early Change in Area Strain Detected by 3D Speckle Tracking Is Associated With Subsequent Cardiotoxicity in Patients Treated With Low Doses of Anthracyclines - Piveta, Rafael B.; Rodrigues, Ana Clara T.; Vieira, Marcelo L. C.; Fischer, Cláudio H.; Afonso, Tania R.; Daminello, Edgar; Cruz, Felipe M.; Galvão, Tatiana F. G.; Filho, Edgar B. L.; Katz, Marcelo; Morhy, Samira S. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate the prognostic impact of the parameters of myocardial deformation using three-dimensional speckle tracking echocardiography (3DSTE) in patients with breast cancer undergoing chemotherapy with low doses of anthracyclines. Background: Chemotherapy-related cardiotoxicity has an important prognostic impact in cancer survivors. 3DSTE has revealed more consistent data than two-dimensional technique and may represent a more accurate tool in the evaluation of myocardial function in patients undergoing chemotherapy. Methods: We evaluated patients with breast cancer treated with anthracyclines (associated or not with trastuzumab) in five stages: baseline, after a cumulative doses of 120 mg/m² and 240 mg/m² of doxorubicin, and then, after 6 months and at least 1 year after anthracyclines. Ultrasensitive troponin I (US-TnI) and a standart echocardiography study were performed at each stage. We analyzed left ventricular ejection fraction (LVEF) by Simpson´s method, two-dimensional speckle tracking (2DSTE) with longitudinal and radial strain values, and 3DSTE with longitudinal, radial and circumferential strain as well as, twist, torsion, rotation and area strain (3DGAS). Cardiotoxicity was defined as a decrease in LVEF by more than 10 percentage points to a value lower than 53%. Results: We evaluated 51 female patients aged 50.6 ± 11 years. After the cumulative dose of 240 mg/m² of doxorubicin US-TnI increased (> 34 pg/mL) in 21 patients (45%, p> 0.001), LVEF remained unchanged (p= 0.178), while 2DSTE longitudinal strain decreased (from -17.8% to -17.1%, p< 0.001) and 3DSTE detected changes in longitudinal, radial, circumferential and area strain. After a lower cumulative dose of doxorubicin (120 mg/m²) 3DGAS (p< 0.001) were the only parameter that changed. In the follow-up, 7 (13%) patients presented decrease in LVEF. 3DGAS early changed to anormal values was associated with subsequent decrease in LVEF (definitive cardiotoxicity). Conclusion: In patients with breast cancer, 3DSTE detected early changes in area strain after very low doses of doxorubicin. The 3DGAS early changed to anormal values was associated with subsequent decrease in LVEF, representing a promising technique to predict chemotherapy-induced cardiomyopathy.